Lithium secondary battery
The lithium secondary battery design incorporates a porous layer on the negative electrode and an ion-conductive polymer adhesive to enhance adhesion durability and maintain ionic conductivity, addressing the challenges of electrode adhesion and thermal stability in existing batteries.
Patent Information
- Application Number
- JP2024555429
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-18
- Filing Date
- 2023-10-31
- Publication Date
- 2025-04-16
AI Technical Summary
Lithium secondary batteries face issues with adhesion durability between electrodes and ion conductivity, leading to partial peeling, wrinkles, and vulnerability to internal short circuits due to insufficient adhesion and thermal instability of separation membranes.
The implementation of a lithium secondary battery design featuring a negative electrode with a porous layer containing a polymeric binder and inorganic fine particles, bonded to a positive electrode via an ion-conductive polymer adhesive portion, which maintains ionic conductivity while enhancing adhesion durability.
This configuration achieves excellent adhesion durability between electrodes without hindering ionic conductivity, thereby improving the overall performance and safety of lithium secondary batteries, especially at high temperatures.
Smart Images

Figure 2025511558000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0155737 dated November 18, 2022, and all contents disclosed in the documents of the Korean Patent Application are incorporated herein by reference.
[0002] The present invention relates to a lithium secondary battery. [Background technology]
[0003] The demand for secondary batteries to be used as driving power sources for mobile phones, laptops, tablet computers, mobile batteries, electric vehicles, personal mobility devices, etc. is steadily increasing due to the increasing functionality of these devices. In particular, lithium secondary batteries, which have a high operating voltage and high energy density per unit weight, are the most widely used.
[0004] A lithium secondary battery generally has a structure in which a chargeable and dischargeable electrode assembly having a positive electrode, a separator, and a negative electrode is attached to a battery case. The positive electrode and the negative electrode are manufactured by coating one or both sides of a metal current collector with a slurry containing an electrode active material, and then drying and rolling the coated surface.
[0005] The separator is one of the important factors that determine the life of a secondary battery, and electrically insulates the positive and negative electrodes. The separator is required to have ion permeability and mechanical strength so that the electrolyte can pass through smoothly. As the application of high-energy lithium secondary batteries expands, the demand for the safety of the separator at high temperatures is also increasing.
[0006] A commonly used separator, which is made of a separator substrate and an inorganic coating layer, does not have sufficient adhesion to the electrode due to the material properties, which causes problems such as partial peeling and wrinkles at the interface between the electrode and the separator. In addition, polyolefin, which is commonly used as a separator substrate, has problems with thermal stability, such as melting at high temperatures.
[0007] To solve these problems, a method has been proposed in which the separator substrate is removed and the separator is constructed only with an inorganic coating film. However, such separators are vulnerable to internal short circuits when applied to electrochemical devices because they still have insufficient adhesive strength with the electrodes and extremely low insulating properties. If an adhesive is applied to the interface between the electrode and separator to supplement the adhesive strength between the separator and the electrode, the ionic conductivity between the electrodes may decrease, causing a loss of capacity in the battery. Furthermore, such separators have a fatal disadvantage in that they easily break due to their low tensile strength and elongation, causing micro-short circuits inside the electrode assembly. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a lithium secondary battery using an electrode assembly having excellent adhesion durability without impairing ionic conductivity between electrodes. [Means for solving the problem]
[0009] According to one embodiment of the invention, A negative electrode portion; a porous layer formed on at least one surface of the negative electrode part, the porous layer including a polymer binder and inorganic fine particles dispersed on the polymer binder; a positive electrode part bonded onto the porous layer via an adhesive part that is continuously or discontinuously arranged; The adhesive portion includes an ion-conductive polymer, The ratio of the area occupied by the adhesive part is 0.02% to 50% based on the area of one surface of the positive electrode part. A lithium secondary battery is provided.
[0010] The lithium secondary battery according to the embodiment of the present invention will be described in more detail below.
[0011] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0012] Unless otherwise defined herein, all technical and scientific terms have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. The terms used in the description of the present invention are merely for the purpose of effectively describing specific specific examples and are not intended to limit the present invention.
[0013] As used herein, the singular forms include the plural forms unless the context clearly dictates to the contrary.
[0014] As used herein, the meaning of "comprising" is to specify particular properties, regions, integers, steps, operations, elements, and / or components and does not exclude the presence or addition of other particular properties, regions, integers, steps, operations, elements, components, and / or groups.
[0015] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated and described in detail below, but it is not intended to limit the present invention to the specific disclosed forms, and it should be understood that the present invention includes any modifications, equivalents, or alternatives falling within the spirit and technical scope of the present invention.
[0016] In this specification, when the positional relationship of two parts is described using, for example, "on," "at the top," "below," "to the side," etc., one or more other parts may be located between the two parts, unless the expressions "directly" or "indirectly" are used.
[0017] In this specification, when a temporal relationship is described using, for example, "after," "following," "next to," or "before," the terms "directly" or "immediately" are not used, and therefore non-consecutive cases may also be included.
[0018] As used herein, the term "at least one" should be understood to include all possible combinations of one or more of the associated items.
[0019] According to one embodiment of the invention, A negative electrode portion; a porous layer formed on at least one surface of the negative electrode part, the porous layer including a polymer binder and inorganic fine particles dispersed on the polymer binder; a positive electrode part bonded onto the porous layer via an adhesive part that is continuously or discontinuously arranged; The adhesive portion includes an ion-conductive polymer, The ratio of the area occupied by the adhesive part is 0.02% to 50% based on the area of one surface of the positive electrode part. A lithium secondary battery is provided.
[0020] As a result of continued research by the present inventors, it has been confirmed that a lithium secondary battery satisfying the above-mentioned constitution can exhibit excellent adhesion durability between electrodes without inhibiting ionic conductivity between the electrodes.
[0021] The lithium secondary battery includes an electrode assembly in which the negative electrode part, the porous layer, and the positive electrode part are sequentially stacked, and in particular, in the electrode assembly, the negative electrode part is integrated with the porous layer, and the positive electrode part is bonded to the porous layer via the adhesive part.
[0022] Preferably, the negative electrode part includes a negative electrode active material layer formed on at least one surface of a negative electrode current collector, the porous layer being formed on the negative electrode active material layer, and the positive electrode part includes a positive electrode active material layer formed on at least one surface of a positive electrode current collector, the porous layer being bonded to the positive electrode active material layer via the adhesive part.
[0023] 1 and 2 are cross-sectional views of an electrode assembly according to an embodiment of the present invention.
[0024] 1 and 2, the negative electrode part 100 may include negative electrode active material layers 130, 137 formed on both sides of a negative electrode current collector 110. Porous layers 250, 257 are formed on the negative electrode part, and are preferably laminated integrally on the negative electrode active material layers 130, 137.
[0025] The positive electrode part 400 may include positive electrode active material layers 430, 437 formed on both sides of a positive electrode current collector 410. The positive electrode part 400 is bonded to the porous layer 250 of the negative electrode part 100 via the adhesive part 300 that is continuously or discontinuously arranged.
[0026] According to an embodiment of the present invention, the area of the region where the adhesive part is arranged is preferably 0.02% to 50% based on the area of one surface of the positive electrode part.
[0027] Specifically, the ratio of the area occupied by the adhesive portion may be 0.02% or more, alternatively 0.05% or more, alternatively 0.1% or more, alternatively 0.5% or more, based on the area of one side of the positive electrode portion; and 50% or less, alternatively 40% or less, alternatively 30% or less, alternatively 20% or less, or alternatively 10% or less.
[0028] In order to ensure sufficient adhesive strength between the negative electrode part and the positive electrode part by the adhesive part, the ratio of the area occupied by the adhesive part is preferably 0.02% or more, or 0.05% or more, or 0.1% or more, or 0.5% or more based on the area of one side of the positive electrode part. However, if the area occupied by the adhesive part is excessive, the ionic conductivity between the electrodes may decrease, and the electrolyte may not smoothly penetrate into the porous layer, resulting in a loss of capacity of the battery. Therefore, the ratio of the area occupied by the adhesive part is preferably 50% or less, or 40% or less, or 30% or less, or 20% or less, or 10% or less based on the area of one side of the positive electrode part.
[0029] Preferably, the ratio of the area occupied by the adhesive part may be 0.02% to 50%, alternatively 0.05% to 50%, alternatively 0.05% to 40%, alternatively 0.1% to 40%, alternatively 0.1% to 30%, alternatively 0.5% to 30%, alternatively 0.5% to 20%, or alternatively 0.5% to 10% based on the area of one side of the positive electrode part.
[0030] According to one implementation, the bonds 300 are disposed continuously or discontinuously.
[0031] As an example, the adhesive portion 300 is disposed continuously or discontinuously along the periphery of the positive electrode part 400. Fig. 4 shows an example in which the adhesive portion 300 is disposed continuously along the periphery of the positive electrode part 400. Figs. 5 and 6 show an example in which the adhesive portion 300 is disposed discontinuously along the periphery of the positive electrode part 400.
[0032] The adhesive portion may be disposed with a constant width w along the periphery of the positive electrode portion. Preferably, the adhesive portion may be disposed with a width w of 50 μm to 700 μm along the periphery of the positive electrode portion.
[0033] Specifically, the width w of the adhesive joint may be 50 μm or more, alternatively 100 μm or more, alternatively 150 μm or more, alternatively 200 μm or more; and 700 μm or less, alternatively 650 μm or less, alternatively 600 μm or less, alternatively 550 μm or less.
[0034] In order to ensure sufficient adhesive strength between the negative electrode part and the positive electrode part by the adhesive part, the width w of the adhesive part is preferably 50 μm or more, or 100 μm or more, or 150 μm or more, or 200 μm or more. However, if the area occupied by the adhesive part is excessive, the ionic conductivity between the electrodes may decrease, and the electrolyte may not smoothly penetrate into the porous layer, which may cause a capacity loss of the battery. Therefore, the width w of the adhesive part is preferably 700 μm or less, or 650 μm or less, or 600 μm or less, or 550 μm or less.
[0035] Preferably, the width w of the bond may be from 50 μm to 700 μm, alternatively from 100 μm to 700 μm, alternatively from 100 μm to 650 μm, alternatively from 150 μm to 650 μm, alternatively from 150 μm to 600 μm, alternatively from 200 μm to 600 μm, alternatively from 200 μm to 550 μm.
[0036] When the adhesive parts are discontinuously arranged along the periphery of the positive electrode part, the adhesive parts may be arranged at regular or irregular intervals d. Preferably, the intervals d between the adhesive parts may be 0.1 mm or more, alternatively 0.5 mm or more, alternatively 1 mm or more; and 20 mm or less, alternatively 15 mm or less, alternatively 10 mm or less.
[0037] In order to allow the electrolyte to sufficiently penetrate into the porous layer, the distance d between the adhesive parts is preferably 0.1 mm or more, or 0.5 mm or more, or 1 mm or more. However, if the distance between the adhesive parts is too large, the adhesive strength between the negative electrode part and the positive electrode part may decrease. Therefore, the distance d between the adhesive parts is preferably 20 mm or less, or 15 mm or less, or 10 mm or less.
[0038] Preferably, the spacing d of the adhesive joints may be from 0.1 mm to 20 mm, alternatively from 0.5 mm to 20 mm, alternatively from 0.5 mm to 15 mm, alternatively from 1 mm to 15 mm, alternatively from 1 mm to 10 mm.
[0039] As another example, the bond may be in the form of a bond pattern that includes two or more bond units.
[0040] The adhesive pattern 350 is a pattern in which a plurality of adhesive units are arranged at predetermined intervals, and connects the negative electrode part, in which the porous layer is integrated, to the positive electrode part.
[0041] In order to provide a suitable adhesive force between the negative electrode part and the positive electrode part through the adhesive pattern, the adhesive pattern preferably includes two or more adhesive units, or four or more adhesive units. The upper limit of the number of the adhesive units included in the adhesive pattern is not particularly limited since it can be appropriately adjusted depending on the areas of the negative electrode part and the positive electrode part.
[0042] The adhesive units may each independently have one or more cross-sectional shapes selected from the group consisting of a circle, an ellipse, a sector, a polygon, and a concave polygon.
[0043] 7 to 10 are cross-sectional views of adhesive patterns according to embodiments of the invention. The adhesive pattern 350 according to FIG. 7 is composed of adhesive units 351 having a circular cross section. The adhesive pattern 350 according to FIG. 8 is composed of adhesive units 351 having a rectangular cross section. The adhesive pattern 350 according to FIG. 9 is composed of adhesive units 351 having a circular cross section and adhesive units 352 having a cross section. The adhesive pattern 350 according to FIG. 10 is composed of adhesive units 351 having a quadrant cross section, adhesive units 352 having a semicircular cross section, and adhesive units 353 having a circular cross section. FIGS. 7 to 10 show a portion of an adhesive pattern as an example, and the adhesive pattern may be expanded and the number of adhesive units may be increased depending on the areas of the negative electrode part and the positive electrode part.
[0044] In order to achieve uniform adhesive strength throughout the adhesive pattern 350, it is preferable that the adhesive patterns are arranged such that the centers of the adhesive units are spaced apart at equal intervals.
[0045] Here, the center of the adhesive unit may be determined based on its cross section. As an example, the center of a circular cross section may be the center of the circle. As another example, the center of an elliptical cross section may be a point where the major axis and minor axis of the ellipse intersect. As yet another example, the center of a sector-shaped cross section, such as a quadrant or semicircle, may be the center of a circle inscribed in the cross section. As yet another example, the center of a polygonal or concave polygonal cross section may be the center of a circle circumscribed in the cross section.
[0046] The adhesive pattern 350 may include adhesive units having two or more cross-sectional shapes selected from the group consisting of a circle, an ellipse, a sector, a polygon, and a concave polygon.
[0047] Here, adhesive units having the same cross-sectional shape may be arranged with the same intervals between their centers. For example, adhesive units 351 having a circular cross section in Fig. 9 are arranged with the same intervals between their centers. And adhesive units 352 having an independent cross section in a cross-shape are arranged with the same intervals between their centers.
[0048] The cross-section of the adhesive unit may have a major axis diameter of 200 nm to 5000 μm.
[0049] Here, the major axis diameter may be determined based on the shape of the cross section of the adhesive unit as follows. As an example, the major axis diameter of a circular cross section means the diameter of the circle. As another example, the major axis diameter of an elliptical cross section means the major axis length of the ellipse. As another example, the major axis diameter of a sector cross section such as a quadrant or semicircle means the length of a segment connecting two points where two radii and an arc meet. As another example, the major axis diameter of a polygonal or concave polygonal cross section means the diameter of a circle circumscribing the cross section.
[0050] According to a realization of the invention, the adhesive portion comprises an ion-conducting polymer.
[0051] The ion-conducting polymer is a compound that has electrochemically stable properties, appropriate adhesiveness, and allows ion migration. By applying the ion-conducting polymer to the adhesive portion, it is possible to minimize the loss of battery capacity due to the adhesive portion.
[0052] Preferably, the ion-conductive polymer may be one or more compounds selected from the group consisting of cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, polyacrylonitrile, polyvinylpyrrolidone, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyacrylonitrile-styrene copolymer, polyvinyl chloride, polyvinyl acetate, polyethylene vinyl acetate copolymer, cyanoethyl pullulan, cyanoethyl sucrose, pullulan, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyethylene glycol, polyethylene glycol dimethyl ether, and carboxymethyl cellulose.
[0053] The adhesive may further include a lithium salt.
[0054] By applying a lithium salt to the adhesive portion together with the ion-conductive polymer, it is possible to achieve further improved ion conductivity.
[0055] The lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(SO2F)2 (hereinafter LiFSI), LiN(CF3SO2)2 (hereinafter LiTFSI), LiCl, LiI, LiB(C2O4)2, etc. Preferably, the lithium salt may be LiPF6, LiFSI, LiTFSI, and mixtures thereof.
[0056] The lithium salt may be included in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the ion conductive polymer. The lithium salt included in this range can exhibit an appropriate effect of improving the ion conductivity of the adhesive part.
[0057] On the other hand, the positive electrode part is obtained by a method of applying a positive electrode material, which is a mixture of a positive electrode active material, a conductive material and a binder, onto at least one surface of a positive electrode current collector, and then drying the applied material to form the positive electrode active material layer.
[0058] The positive electrode current collector may be any material known in the art to which the present invention pertains that has conductivity without inducing a chemical change in the secondary battery. For example, the positive electrode current collector may be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.
[0059] Preferably, the positive electrode current collector has a thickness of 3 μm to 500 μm. In order to increase the adhesive strength of the positive electrode material, the positive electrode current collector may have a fine unevenness formed on its surface. The positive electrode current collector may have various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc.
[0060] The positive electrode active material may be any material capable of reversibly inserting and extracting lithium ions without any particular limitation. For example, the positive electrode active material may be a composite oxide or phosphate containing lithium and a metal selected from cobalt, manganese, nickel, iron, or a combination thereof.
[0061] As another example, the positive electrode active material may be a compound represented by any one of the following chemical formulas: Li a A 1-b R b D2(0.90≦a≦1.8, 0≦b≦0.5);Li a E 1-b R b O 2-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);LiE 2-b R b O 4-c D c (0≦b≦0.5, 0≦c≦0.05);Lia Ni 1-b-c Co b R c D d (0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d≦2);Li a Ni 1-b-c Co b R c O 2-d Z d (0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d<2);Li a Ni 1-b-c Co b R c O 2-d Z2(0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d<2);Li a Ni 1-b-c Mr b R c D d (0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d≦2);Li a Ni 1-b-c Mr b R c O 2-d Z d (0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d<2);Li a Ni 1-b-c Mr b R c O 2-d Z2(0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.05、0 <d<2);Li a Ni b HAVE BEEN c G d O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0.001≦d≦0.1.);Li a Ni b Co c Mr d G e O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0≦d≦0.5、0.001≦e≦0.1);Li a NiG b O2(0.90≦a≦1.8、0.001≦b≦0.1);Li a CoG bO2(0.90≦a≦1.8, 0.001≦b≦0.1);Li a MnG b O2(0.90≦a≦1.8, 0.001≦b≦0.1);Li a Mn2G b O4(0.90≦a≦1.8, 0.001≦b≦0.1);QO2;QS2;LiQS2;V2O5;LiV2O5;LiTO2;LiNiVO4;Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) Fe2(PO4)3 (0≦f≦2); and LiFePO 4.
[0062] In the above formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0063] Of course, the positive electrode active material may have a coating layer on the surface thereof, or the positive electrode active material may be mixed with the positive electrode active material having a coating layer. The coating element contained in the coating layer may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof.
[0064] According to an embodiment, the positive electrode active material may be included in an amount of 80 wt% to 95 wt% based on the total weight of the positive electrode material. Preferably, the positive electrode active material may be included in an amount of 82 wt% to 95 wt%, 82 wt% to 93 wt%, 85 wt% to 93 wt%, or 85 wt% to 90 wt% based on the total weight of the positive electrode material.
[0065] The thickness of the positive electrode active material layer may be determined within a range that does not impair the electrical characteristics of the lithium secondary battery. As a non-limiting example, the positive electrode active material layer may have a thickness of 10 μm to 500 μm.
[0066] The conductive material is used to impart electrical conductivity to the electrode.
[0067] The conductive material may be any material that has electronic conductivity without causing chemical changes in the battery and that can be used without any particular limitations. Non-limiting examples of the conductive material include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskey such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; and conductive polymers such as polyphenylene derivatives. The conductive material may be one or a mixture of two or more of the above-mentioned examples.
[0068] The content of the conductive material may be adjusted within a range that does not cause a decrease in the capacity of the battery while exhibiting an appropriate level of conductivity, and preferably, the content of the conductive material may be 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the cathode material.
[0069] The binder is used to firmly attach the positive electrode material to the positive electrode current collector.
[0070] Non-limiting examples of the binder include polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon resin, etc. The binder may be one or a mixture of two or more of the above-mentioned examples.
[0071] The content of the binder may be adjusted within a range that does not cause a decrease in the capacity of the battery while exhibiting an appropriate level of adhesiveness, and preferably, the content of the binder may be 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the cathode material.
[0072] The negative electrode part and the porous layer are obtained by a method of coating a negative electrode material, which is a mixture of a negative electrode active material, a conductive material, and a binder, on at least one surface of a negative electrode current collector, and drying the coating to form the negative electrode active material layer, and coating a mixture containing a polymer binder and inorganic fine particles on the negative electrode active material layer, and drying the coating to form the porous layer.
[0073] The negative electrode current collector included in the negative electrode part replaces the contents of the positive electrode current collector, and the conductive material and binder included in the negative electrode part replace the contents of the positive electrode part.
[0074] The negative electrode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0075] Examples of the material capable of reversibly intercalating and deintercalating the lithium ions include carbonaceous materials such as crystalline carbon, amorphous carbon, or a mixture thereof. Specifically, the carbonaceous material may be natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitches, mesophase pitch based carbon fiber, carbon microspheres, petroleum or coal tar pitch derived cokes, soft carbon, and hard carbon.
[0076] The lithium metal alloy may be an alloy of lithium with a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.
[0077] The substances capable of being doped and undoped with lithium may be Si, Si-C composite, SiOx (0 < x < 2), Si-Q alloy (wherein Q is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof; provided that Si is excluded), Sn, SnO2, Sn-R alloy (wherein R is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof; provided that Sn is excluded), etc. And as the substances capable of being doped and undoped with lithium, at least one of the above examples and SiO2 may be mixed and used. The Q and R may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, etc.
[0078] And the transition metal oxide may be vanadium oxide, lithium vanadium oxide, lithium titanate, etc.
[0079] Preferably, the negative electrode active material may contain one or more compounds selected from the group consisting of carbonaceous materials and silicon compounds. Here, the carbonaceous material is one or more substances selected from the group consisting of natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, carbon microspheres, petroleum or coal-based coke, softened carbon, and hardened carbon exemplified above. And the silicon compound may be a compound containing Si exemplified above, that is, Si, Si-C composite, SiOx (0 < x < 2), the Si-Q alloy, a mixture thereof, or a mixture of at least one of these and SiO2.
[0080] According to an embodiment, the negative electrode active material may be included in an amount of 85 wt% to 98 wt% based on the total weight of the negative electrode material. Preferably, the content of the negative electrode active material may be 85 wt% to 97 wt%, 87 wt% to 97 wt%, 87 wt% to 95 wt%, or 90 wt% to 95 wt% based on the total weight of the negative electrode material.
[0081] The porous layer comprises a polymeric binder and inorganic fine particles dispersed on the polymeric binder.
[0082] The polymer binder may be one that gels when impregnated with a liquid electrolyte and exhibits a high degree of swelling. The electrolyte injected after assembly of the secondary battery permeates the polymer binder, and the polymer binder that holds the absorbed electrolyte has electrolyte ion conduction ability. Therefore, the polymer binder has a solubility index of 15 to 45 MPa. 1 / 2 A polymer in which
[0083] As an example, the polymer binder may be one or more compounds selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
[0084] The inorganic fine particles form micropores due to empty spaces between the particles, maintain their physical shape at high temperatures, and are electrochemically stable.
[0085] The inorganic fine particles preferably do not undergo oxidation and / or reduction reactions in the operating voltage range of a secondary battery (e.g., 0 to 5 V based on Li / Li+). The inorganic fine particles preferably have high electrolyte ion transfer ability. The inorganic fine particles preferably have as low a density as possible so that they can be well dispersed in the polymer binder. And, the inorganic fine particles preferably have a high dielectric constant so that they can contribute to increasing the degree of dissociation of the electrolyte salt in the electrolyte.
[0086] Preferably, the inorganic fine particles may be one or more types selected from the group consisting of inorganic particles having a dielectric constant of 1 or more, inorganic particles having piezoelectricity, and inorganic particles having lithium ion transport ability.
[0087] As an example, inorganic particles such as SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, and SiC have a dielectric constant of 1 or more and can be preferably applied as the inorganic fine particles.
[0088] As another example, the inorganic particles having piezoelectricity are non-conductors at normal pressure, but when a certain pressure is applied, they become conductive due to a change in their internal structure. The piezoelectric inorganic particles have a high dielectric constant characteristic of 100 or more. In addition, when a certain pressure is applied to the piezoelectric inorganic particles to stretch or compress them, charges are generated and one side is charged positively (+) and the other side is charged negatively (-), generating a potential difference between the two sides. Due to the characteristics of the piezoelectric inorganic particles, when an internal short circuit occurs in the electrodes of the secondary battery due to an external impact, it is possible to prevent the positive electrode and the negative electrode from coming into direct contact, thereby enabling a gradual decrease in voltage and improved safety. Examples of the piezoelectric inorganic particles include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x Lax Zr 1-y Ti y O3 (PLZT), Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3 (PMN - PT), and inorganic particles such as HfO2 can be preferably applied.
[0089] As another example, the inorganic particles having the lithium ion transfer ability refer to inorganic particles that contain lithium element and have a function of moving lithium ions without storing lithium. The inorganic particles having the lithium ion transfer ability can improve the conductivity of lithium ions in the battery. Such inorganic particles include Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z (0 < x < 3, 0 < y < 3, 0 < z < 7) and the like can be cited as examples.
[0090] Preferably, the inorganic fine particles are SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, SiC, BaTiO3, Pb(Zr,Ti)O3, Pb 1-xLa x Zr 1-y Ti y O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3, HfO2, Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z It may be one or more selected from the group consisting of (0 < x < 3, 0 < y < 3, 0 < z < 7).
[0091] The inorganic fine particles preferably have a particle size of 0.001 μm to 10 μm. To ensure dispersibility in the porous layer, the inorganic fine particles preferably have a particle size of 0.001 μm or more. However, when the particle size of the inorganic fine particles is excessively large, the thickness of the porous layer increases and the mechanical properties deteriorate, and there is a possibility of internal short - circuit during charge and discharge of the secondary battery due to an excessively large pore size. Therefore, the inorganic fine particles preferably have a particle size of 10 μm or less.
[0092] The porous layer may contain 10 to 99 wt % of the inorganic fine particles and 1 to 90 wt % of the polymer binder. The inorganic fine particles are preferably contained in an amount of 10 wt % or more so that the porous layer can have appropriate porosity and insulating properties. However, if the inorganic fine particles are contained in an excessive amount, the mechanical properties of the porous layer may be deteriorated due to weakened adhesive strength. Therefore, the inorganic fine particles are preferably contained in an amount of 99 wt % or less.
[0093] Here, the cross-sectional areas of the negative electrode current collector, the negative electrode active material layer, and the porous layer may be the same, or the cross-sectional areas of the negative electrode active material layer and the porous layer may be 80% to 120% or 90% to 110% of the cross-sectional area of the negative electrode current collector.
[0094] The method of bonding the positive electrode part onto the porous layer through the adhesive part may be performed by a conventional lamination method. For example, the adhesive part may be disposed on one surface of either the porous layer or the positive electrode part, and then the other one may be laminated thereon. The adhesive part may be formed by a method such as coating, dispensing, transfer, deposition, printing, or spraying.
[0095] The thicknesses of the negative electrode active material layer, the porous layer, and the adhesive may be determined within a range that does not impair the electrical characteristics of a lithium secondary battery including the negative electrode. As a non-limiting example, the negative electrode active material layer may have a thickness of 10 μm to 500 μm, the porous layer may have a thickness of 5 μm to 200 μm, and the adhesive may have a thickness of 10 μm to 300 μm.
[0096] The area and ratio of the negative electrode part and the positive electrode part may vary depending on the type or shape of the battery. For example, the size of the positive electrode part may be the same as the size of the negative electrode part. Alternatively, the size of the positive electrode part may be smaller or larger than the size of the negative electrode part. Preferably, the ratio of the cross-sectional area of the positive electrode part based on the cross-sectional area of the negative electrode part may be in the range of 0.7 to 1.0, or 0.8 to 1.0, or 0.8 to 1.0.
[0097] According to one implementation, the lithium secondary battery may include a plurality of electrode assemblies as shown in FIG.
[0098] Referring to FIG. 3, one electrode assembly unit S1 and another electrode assembly unit S2 may be coupled to each other via an adhesive part 300''. Here, the electrode assembly unit S1 includes a negative electrode part 100 integrated with porous layers 250, 257 and a positive electrode part 400 coupled to the porous layer 250 via an adhesive part 300. The electrode assembly unit S2 includes a negative electrode part 100' integrated with porous layers 250', 257' and a positive electrode part 400' coupled to the porous layer 250' via an adhesive part 300'.
[0099] According to one embodiment of the invention, the lithium secondary battery may include an electrode assembly including the negative electrode portion, the porous layer, and the positive electrode portion, an electrolyte, and a battery case that hermetically houses the electrode assembly and the electrolyte.
[0100] The lithium secondary battery includes the above-described electrode assembly, and thus exhibits excellent durability and stable performance.
[0101] The lithium secondary battery can be used as an energy supply source with improved performance and safety in the field of portable electronic devices such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras, and in the field of transportation means such as electric cars, electric motorcycles, and personal mobility devices.
[0102] The lithium secondary battery may include the electrode assembly and a battery case in which the electrode assembly is built in. The electrode assembly may be impregnated with an electrolyte.
[0103] The lithium secondary battery may have various shapes, such as a square shape, a cylindrical shape, a pouch shape, and the like.
[0104] The electrolyte may be any electrolyte known in the art to which the present invention pertains that is applicable to lithium secondary batteries, without any particular limitations. For example, the electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.
[0105] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt.
[0106] The non-aqueous organic solvent may be any solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery.
[0107] Specifically, the non-aqueous organic solvent may be an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; an ether-based solvent such as dibutyl ether and tetrahydrofuran; a ketone-based solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (propylene carbonate). The solvent may be a carbonate solvent such as polycarbonate (PC); an alcohol solvent such as ethyl alcohol and isopropyl alcohol; a nitrile such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; and sulfolane.
[0108] Among the above examples, carbonate-based solvents are preferably used as the non-aqueous organic solvent.
[0109] In particular, in consideration of the charge / discharge performance of the battery and the compatibility with the sacrificial positive electrode material, a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant (e.g., ethylene carbonate, propylene carbonate) and a linear carbonate having low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate) can be preferably used as the non-aqueous organic solvent. In this case, it may be advantageous to use a mixture of the cyclic carbonate and the linear carbonate in a volume ratio of 1:1 to 1:9 for the expression of the above-mentioned performance.
[0110] As the non-aqueous organic solvent, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 to 1:10; or a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1-3:1 to 9:1 can be preferably used.
[0111] The lithium salt contained in the electrolyte is dissolved in the non-aqueous organic solvent and acts as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to promote the movement of lithium ions between the positive electrode and the negative electrode.
[0112] Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiFSI, LiTFSI, LiCl, LiI, LiB(C2O4)2, etc. Preferably, the lithium salt may be LiPF6, LiFSI, LiTFSI, and mixtures thereof.
[0113] The lithium salt may be contained in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt contained in this concentration range provides the electrolyte with appropriate conductivity and viscosity, thereby enabling the electrolyte to exhibit excellent electrolyte performance.
[0114] Optionally, the electrolyte may contain additives for the purposes of improving the life characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery.
[0115] For example, the additive may be a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivative, sulfur, quinoneimine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The additive may be included in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte. Effect of the Invention
[0116] According to the present invention, there is provided an electrode assembly for a lithium secondary battery having excellent adhesion durability without inhibiting ionic conductivity between electrodes, and a secondary battery including the same. [Brief description of the drawings]
[0117] [Figure 1] 1 is a cross-sectional view of an electrode assembly according to an embodiment of the invention. [Diagram 2] 1 is a cross-sectional view of an electrode assembly according to an embodiment of the invention. [Diagram 3] 1 is a cross-sectional view of an electrode assembly according to an embodiment of the invention. [Figure 4] FIG. 2 is a cross-sectional view of a bond according to an embodiment of the invention. [Diagram 5] FIG. 2 is a cross-sectional view of a bond according to an embodiment of the invention. [Figure 6] FIG. 2 is a cross-sectional view of a bond according to an embodiment of the invention. [Figure 7] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Figure 8] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Figure 9] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. [Figure 10] 1 is a cross-sectional view of a bond pattern according to an embodiment of the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0118] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention. However, these are presented as examples to help understand the invention. The following examples are not intended to limit the scope of the invention in any way, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and technical concept of the present invention.
[0119] Example 1 An aqueous active material slurry was prepared, which was composed of 86 parts by weight of graphite active material, which was a mixture of artificial graphite and natural graphite in a ratio of 3:7, 7 parts by weight of acetylene black as a conductive material, and 7 parts by weight of SBR (styrene butadiene rubber) as a binder. The active material slurry was applied to the entire surface of a copper current collector (thickness 100 μm, width 50 mm, length 90 mm) using a comma coater and dried, and then applied to the other side of the current collector in the same manner and dried. This was rolled to form a negative active material layer (thickness 50 μm) with a porosity of 24%.
[0120] Aluminum oxide powder (average particle size: 400 nm) was added to a 10 wt% polyvinylidene fluoride (PVDF) solution in N-methyl-2-pyrrolidinone (NMP) and milled using a beads mill to prepare an inorganic fine particle dispersion. The weight ratio of aluminum oxide to PVDF was 90:10.
[0121] The inorganic fine particle dispersion liquid was coated on the negative electrode active material layer to a thickness of 20 μm using a doctor blade, and then dried at 100° C. for 5 minutes to prepare a negative electrode integrated porous layer.
[0122] An adhesive solution was prepared by dispersing an adhesive (cyanoethylated polyvinyl alcohol; Mw 50,000 g / mol; manufactured by ECO Chemical) at a solid concentration of 20 wt%. The adhesive solution was used to form an adhesive dot pattern (a pattern consisting of adhesive units with a circular cross section; adhesive pattern width 45 mm, length 80 mm; total of 45 adhesive units with a radius of 1 mm and a thickness of 100 μm arranged in a 5*9 arrangement) on the porous layer.
[0123] A mixture of 94 parts by weight of LiNiCoMnO2 (Ni:Co:Mn=8:1:1) as a positive electrode active material, 3 parts by weight of conductive carbon black (Super P;IMERYS Graphite & Carbon) as a conductive material, and 3 parts by weight of polyvinylidene fluoride as a binder was added to NMP to prepare a uniformly dispersed slurry. The slurry was applied to both sides of an aluminum current collector (thickness 100 μm) to a thickness of 50 μm, which was then dried and rolled to prepare a positive electrode plate. The positive electrode plate was punched out using a die punching machine to prepare a positive electrode part (width 47.5 mm, length 81 mm).
[0124] The positive electrode part was placed on the porous layer on which the adhesive dot pattern was formed, and was bonded using the adhesive dot pattern as a medium to manufacture an electrode assembly. Here, the ratio of the area of the adhesive dot pattern to the area of one side of the positive electrode part was 3.14%.
[0125] The electrode assembly was housed in a pouch to form a small cell, and an electrolyte was injected into the pouch to fabricate a lithium secondary battery stack cell.
[0126] The electrolyte used was a non-aqueous organic solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 1:2:1, with 1.0 M LiPF6 and 2 wt % vinylene carbonate (VC) dissolved in it.
[0127] Example 2 A lithium secondary battery stack cell was fabricated in the same manner as in Example 1, except that the diameter of the adhesive unit in the adhesive dot pattern was reduced so that the area ratio of the adhesive dot pattern was 1.0%.
[0128] Example 3 A lithium secondary battery stack cell was manufactured in the same manner as in Example 1, except that the diameter of the adhesive unit in the adhesive dot pattern was increased so that the area ratio of the adhesive dot pattern was 7.0%.
[0129] Example 4 A lithium secondary battery stack cell was manufactured in the same manner as in Example 1, except that the adhesive solution was continuously applied along the periphery of the positive electrode part with a width of 0.5 mm using a dispensing device, and the ratio of the area occupied by the adhesive part based on the area of one side of the positive electrode part was 3.31%.
[0130] Example 5 A lithium secondary battery stack cell was fabricated in the same manner as in Example 4, except that the width of the adhesive solution continuously applied along the periphery of the positive electrode part using a dispensing device was reduced so that the ratio of the area occupied by the adhesive part was 1.0%.
[0131] Example 6 A lithium secondary battery stack cell was manufactured in the same manner as in Example 4, except that the width of the adhesive solution continuously applied along the periphery of the positive electrode part using a dispensing device was increased so that the ratio of the area occupied by the adhesive part was 7.0%.
[0132] Comparative Example 1 A lithium secondary battery stack cell was fabricated in the same manner as in Example 1, except that the diameter of the adhesive unit in the adhesive dot pattern was reduced so that the ratio of the area occupied by the adhesive dot pattern was 0.01%.
[0133] However, in Comparative Example 1, the positive electrode part was not adhered onto the porous layer, and it was impossible to assemble a lithium secondary battery stack cell.
[0134] Comparative Example 2 A lithium secondary battery stack cell was fabricated in the same manner as in Example 1, except that the diameter of the adhesive unit in the adhesive dot pattern was increased so that the area ratio of the adhesive dot pattern was 52%.
[0135] Experimental Example The lithium secondary battery stack cells obtained in the examples and comparative examples were charged at 0.1C in CC-CV mode at 25°C until the voltage reached 4.2V, and the voltage was maintained in CV mode until the voltage reached 0.05C. Thereafter, the cells were discharged at 0.1C until the voltage reached 2.5V for activation. Thereafter, the cells were charged at 0.33C until the voltage reached 4.2V, and then discharged at 0.1C, 0.33C, 1C, 2C, and 3C until the voltage reached 2.5V to confirm the high rate discharge characteristics. The following values are ratios calculated based on the 0.1C capacity in Example 1.
[0136] [Table 1]
[0137] Referring to Table 1, it was confirmed that the lithium secondary batteries of the Examples exhibited superior adhesion durability and high rate discharge characteristics compared to the Comparative Examples.
[0138] In the comparative example 1, the positive electrode part was not attached onto the porous layer, and it was impossible to assemble a lithium secondary battery stack cell. The lithium secondary battery of the comparative example 2 showed inferior high rate discharge characteristics compared to the examples.
[0139] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary skill in the art to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims set forth below. [Explanation of symbols]
[0140] 100, 100': Negative electrode 110, 110': Negative electrode current collector 130, 130', 137, 137': Negative electrode active material layer 250, 250', 257, 257': Porous layer 300, 300', 300'': Adhesive part w: width of adhesive joint d: Spacing of adhesive joints 350: Bonding pattern 351, 352, 353: Adhesive unit 400, 400': Positive electrode 410, 410': Positive electrode current collector 430, 430', 437, 437': Positive electrode active material layer S1, S2: Electrode assembly unit
Claims
1. A negative electrode portion; a porous layer formed on at least one surface of the negative electrode part, the porous layer including a polymer binder and inorganic fine particles dispersed on the polymer binder; a positive electrode part bonded onto the porous layer via an adhesive part that is continuously or discontinuously arranged; The adhesive portion includes an ion-conductive polymer, The ratio of the area occupied by the adhesive portion is 0.02% to 50% based on the area of one surface of the positive electrode portion. Lithium secondary battery.
2. 2. The lithium secondary battery according to claim 1, wherein the ion-conducting polymer is one or more compounds selected from the group consisting of cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, polyacrylonitrile, polyvinylpyrrolidone, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyacrylonitrile-styrene copolymer, polyvinyl chloride, polyvinyl acetate, polyethylene vinyl acetate copolymer, cyanoethyl pullulan, cyanoethyl sucrose, pullulan, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyethylene glycol, polyethylene glycol dimethyl ether, and carboxyl methyl cellulose.
3. The lithium secondary battery according to claim 1 , wherein the adhesive portion further contains a lithium salt.
4. The lithium secondary battery according to claim 1 , wherein the adhesive portion is disposed continuously or discontinuously along a periphery of the positive electrode portion.
5. The lithium secondary battery according to claim 1 , wherein the adhesive portion is disposed along the periphery of the positive electrode portion with a width of 50 μm to 700 μm.
6. 2. The lithium secondary battery according to claim 1, wherein the adhesive portions are discontinuous and disposed at regular or irregular intervals along the periphery of the positive electrode portion.
7. 10. The lithium secondary battery of claim 1, wherein the adhesive comprises a adhesive pattern including two or more adhesive units.
8. The lithium secondary battery according to claim 7 , wherein the adhesive units each independently have one or more cross-sectional shapes selected from the group consisting of a circle, an ellipse, a sector, a polygon, and a concave polygon.
9. The lithium secondary battery according to claim 7 , wherein the adhesive pattern is arranged such that the centers of the adhesive units are equally spaced apart.
10. 8. The lithium secondary battery according to claim 7, wherein the cross section of the adhesive unit has a major axis diameter of 200 nm to 5000 μm.
11. the negative electrode part includes a negative electrode active material layer formed on at least one surface of a negative electrode current collector, The porous layer is formed on the negative electrode active material layer. The lithium secondary battery according to claim 1 .
12. The positive electrode part includes a positive electrode active material layer formed on at least one surface of a positive electrode current collector, the porous layer and the positive electrode active material layer are bonded to each other via an adhesive pattern; The lithium secondary battery according to claim 1 .
13. 2. The lithium secondary battery of claim 1, wherein the polymer binder is at least one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
14. The inorganic fine particles are SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2 O 3 , boehmite (AlO(OH)), Al(OH) 3 , TiO 2 , SiC, BaTiO 3 , Pb(Zr,Ti)O 3 , Pb 1-x La x Zr 1-y Ti y O 3 , Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 , HfO 2 , Li 3 PO 4 , Li x Ti y (PO 4 ) 3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO 4 ) 3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO 3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z 2. The lithium secondary battery according to claim 1, wherein the x and y are one or more elements selected from the group consisting of: (0<x<3, 0<y<3), 0<z<7).
15. The lithium secondary battery according to claim 1 , wherein the inorganic fine particles have a particle size of 0.001 μm to 10 μm.
16. 2. The lithium secondary battery of claim 1, wherein the porous layer comprises 10 to 99 wt % of the inorganic fine particles and 1 to 90 wt % of the polymer binder.
17. an electrode assembly including the negative electrode part, the porous layer, and the positive electrode part; An electrolyte; a battery case that hermetically houses the electrode assembly and the electrolyte; The lithium secondary battery according to claim 1 ,
Citation Information
Patent Citations
Lithium battery pole piece and preparation method and application thereof
CN113328063A
Cell and its manufacturing method
JP2002015773A
Lithium-based electrochemical device having a ceramic separator bonded with an ion-conducting adhesive
JP2005529468A
Secondary battery
JP2018055951A
Separator laminate for lithium secondary battery, electrode assembly including the same, and lithium secondary battery
JP2022519361A